2011
DOI: 10.1097/ppo.0b013e318227c811
|View full text |Cite
|
Sign up to set email alerts
|

Informatics-Enabled Behavioral Medicine in Oncology

Abstract: For the practicing physician, the behavioral implications of preventing, diagnosing, and treating cancer are many and varied. Fortunately, an enhanced capacity in informatics may help create a redesigned ecosystem in which applying evidence-based principles from behavioral medicine will become a routine part of care. Innovation to support this evolution will be spurred by the “meaningful use” criteria stipulated by the Health Information Technology for Economic and Clinical Health (HITECH) Act of 2009, and by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 81 publications
(98 reference statements)
0
8
0
Order By: Relevance
“…Although both system types are appropriate in oncology, there is a need for long-term monitoring across the cancer care continuum. 15 Our study identified increased development of patient-centered systems over the past 5 years, which may be due in part to this report, as well as the increasing ability to electronically capture patient data in care settings. Ideally, it would be useful for e-PRO systems to monitor patients throughout the course of care while capturing detailed information about patients' responses to specific treatments in order to balance these important objectives.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although both system types are appropriate in oncology, there is a need for long-term monitoring across the cancer care continuum. 15 Our study identified increased development of patient-centered systems over the past 5 years, which may be due in part to this report, as well as the increasing ability to electronically capture patient data in care settings. Ideally, it would be useful for e-PRO systems to monitor patients throughout the course of care while capturing detailed information about patients' responses to specific treatments in order to balance these important objectives.…”
Section: Discussionmentioning
confidence: 92%
“…Although many large cancer centers have resources necessary to develop, run, and maintain an e-PRO system, limited capacity in smaller rural and community-based practice settings, where real-time monitoring is especially useful, can pose an issue. 15,20 As systems move further away from clinical settings, managing score-based alerts becomes challenging. System alerts occurring outside the clinic can be in the form of an electronic communication between patient and provider.…”
Section: Data Collection Featuresmentioning
confidence: 99%
“…As treatment progresses, the oncologist may introduce the patient to a nurse navigator to help schedule appointments, arrange for tests, and report symptoms. These services provide informational support from the environment to complement the patient's evolving knowledge about their condition(s) [27].…”
Section: A Health Systems Perspective On Health Literacymentioning
confidence: 99%
“…Likewise, the National Institutes of Health is partnering with the National Science Foundation to create improved participatory platforms for turning "Big Data" into practicable knowledge. Ultimately, the goal is to help coordinate efforts and improve situational awareness with highly accessible community dashboards and other types of data visualizations (68,69). Kreuter noted that the best innovations in cancer communication do not necessarily achieve broad uptake by researchers, public health and clinical practitioners, and policy makers (70).…”
Section: Goal 3: Align Systemsmentioning
confidence: 99%